Exploring the inequalities experienced by health and care workforce and their bases - A scoping review protocol. - Roomi Aziz; Anuj Kapilashrami; Reza Majdzadeh (PLoS ONE)
Planning for investment in human resources for health (HRH) is critical to achieve Universal Health Coverage (UHC) and establish a sustainable health system. Informed planning warrants a better understanding of the health labour market (HLM) to tackle a variety of health and care workforce challenges: from addressing critical supply shortage, to ensuring optimal skills mix and distribution, and addressing motivation and performance challenges. Scant evidence around the overall role of socioeconomic and cultural factors like gender, race, marital status, citizenship (migrant) status, workplace hierarchy etc. in determining workforce composition, deployment, distribution, retention, un- and underemployment, sub-optimal work environments and other factors in the 'HRH crisis' warrants further exploration. This scoping review protocol aims to map and present the available evidence on inequalities experienced by health and care workforce, the socio-economic, cultural and other bases of these inequalities, and their outcomes/ consequences. PubMed, Web of Science, CINAHL and SCOPUS will be used to identify relevant literature. All types of published study designs in English language will be included if they discuss any inequality experienced by any category of health and care workers. Elaborate keyword categories for health and care workers and inequalities context have been developed, tested and reduced to the near-final search string. Eligible articles will be charted using the Joanna Briggs Institute checklist. The sample data extraction chart in JBI manual will be used as a basic skeleton with fields added to it to serve the needs of the scoping review. Descriptive analysis will be performed, depicting basic frequencies. While no further analysis has been advised in the JBI and PRISMA protocol, thematic analysis will be undertaken; following the Braun and Clarke's method with some modification and open coding as suggested by Maquire and Delahunt.